2004
DOI: 10.5194/angeo-22-3971-2004
|View full text |Cite
|
Sign up to set email alerts
|

Combined wind profiler-weather radar observations of orographic rainband around Kyushu, Japan in the Baiu season

Abstract: Abstract.A special observation campaign (X-BAIU), using various instruments (wind profilers, C-band weather radars, X-band Doppler radars, rawinsondes, etc.), was carried out in Kyushu (western Japan) during the Baiu season, from 1998 to 2002. In the X-BAIU-99 and -02 observations, a line-shaped orographic rainband extending northeastward from the Koshikijima Islands appeared in the low-level strong wind with warm-moist airs. The weather radar observation indicated that the rainband was maintained for 11 h. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Some previous studies indicated that the formation and maintenance mechanisms of these two lines were related to the topography of Koshikijima Islands and Nagasaki Peninsula (Morita et al 1998;Yoshizaki et al 2000;Tashiro 2004;Umemoto et al 2004). Meanwhile, Kato and Niino (1998) showed from numerical experiments that those mechanisms of the Koshikijima line hardly depended on the topography of Koshikijima Islands.…”
Section: Introductionmentioning
confidence: 98%
“…Some previous studies indicated that the formation and maintenance mechanisms of these two lines were related to the topography of Koshikijima Islands and Nagasaki Peninsula (Morita et al 1998;Yoshizaki et al 2000;Tashiro 2004;Umemoto et al 2004). Meanwhile, Kato and Niino (1998) showed from numerical experiments that those mechanisms of the Koshikijima line hardly depended on the topography of Koshikijima Islands.…”
Section: Introductionmentioning
confidence: 98%
“…However, the development of line-shaped convective systems occurs in limited areas within a meso-a-scale system, because these systems are strongly influenced by orography. On the one hand, several authors pointed out the importance of orographic wave disturbances that cause line-shaped precipitation systems with rainfall exceeding 150 mm day À1 around Kyushu, called Koshikijima and Nagasaki lines, when an intense southerly or southwesterly from the tropics in the lower layer with a height of about 1 km is maintained for 12 h by meso-a-scale systems (Kato et al 2003;Tashiro 2004;Umemoto et al 2004;Kato 2005). On the other hand, several authors pointed out that such a line-shaped convective system develops around a meso-b-scale (20-200 km horizontal scale) low.…”
Section: Introductionmentioning
confidence: 99%